Effect of Information Quality on Accounting Firms Performance in Libya - Omer, Gumaa Alfaitori E. (2011)
The relationship between information and decision-making is a complex. More recently, researchers have suggested a relationship between the quality of information and the quality of decision-making, which is important to enhance the firm performance. Thus this study has investigated the impact of information quality on accounting firm performance in Libya. To investigate the relationship of information quality and accounting firm performance researcher has collected 120 samples from different accounting firms in Tripoli in Libya. It has found that there are positive relationship between information quality and accounting firm performance in Libya.